The Effect of High Intensity Focused Ultrasound Keratoplasty on Rabbit Anterior Segment - Menglei Wang; Meixuan Li; Pisong Yan; Qiang Luo; Yu Zhang; Zhiyu Du (Journal of Ophthalmology)
Purpose. To evaluate the safety of high-intensity focused ultrasound keratoplasty as a treatment for presbyopia by examining its effect on the rabbit anterior segment. Methods. The right corneas of 36 New Zealand rabbits were treated with HIFU keratoplasty. The animals were sacrificed at 1, 7, 15, 30, 60, and 90 days after operation. Collagen type I, MMP-2, and MMP-9 were evaluated using immunohistochemistry. For the detection of apoptosis, the TUNEL method was applied. The SOD and MDA levels were analyzed with assay kits. Results. Collagen type I, MMP-2, and MMP-9 levels were altered after the operation but returned to normal within 90 days. The apoptotic index (AI) of the corneal cells decreased from 1 to 30 days gradually. No apoptosis was observed in the epithelial cells of the lens, and the SOD and MDA levels were normal at any time point. Conclusion. After HIFU keratoplasty, the histomorphology of the cornea changed, the corneal collagen type I levels decreased, the corneal MMP-2 and MMP-9 levels increased, and the corneal cells underwent apoptosis for a period of time. Ninety days after the operation, the levels returned to normal, and the lenses were not affected. Thus, HIFU presents good biological safety for eyes.